Kinematic alterations after two high-intensity intermittent training protocols in endurance runners - Felipe García-Pinillos; Alejandro Molina-Molina; Juan A. Párraga-Montilla; Pedro A. Latorre-Román (Elsevier, 2019)
Purpose: This study aimed to evaluate running kinematic characteristics during the early and late stages of 2 high-intensity intermittent training (HIIT) protocols with similar external load but different average running pace, as well as to compare the fatigue-induced changes during both HIIT protocols at a kinematic level. Methods: Eighteen endurance runners were tested on a track on 2 occasions: 10 runs of 400 m with 90-120 s recovery between running bouts (10 × 400 m), and 40 runs of 100 m with 25-30 s recovery between running bouts (40 × 100 m). Heart rate was monitored during both protocols; blood lactate accumulation and rate of perceived exertion were recorded after both exercises. A high-speed camera was used to measure sagittal-plane kinematics at the first and last runs during both HIIT protocols. The dependent variables were spatial-temporal parameters (step length and contact and flight time), joint angles during support (relative angles of the hip, knee, and ankle), and foot strike pattern. Results: High levels of exhaustion were reached by the athletes during both workouts (blood lactate accumulation >12 mmol/L, rate of perceived exertion >15; peak heart rate (HRpeak) > 176 bpm). A within-protocol paired t test (first vs. last run) revealed no significant changes (p ≥ 0.05) in kinematic variables during any of the HIIT sessions. A between-protocol comparison with the first run of each protocol revealed the effect of running speed on kinematics: +2.44 km/h during the 40 × 100 m: shorter contact and flight time (p  ≤  0.01) and longer step length (p = 0.001); greater hip flexion (p = 0.031) and ankle extension (p = 0.001) at initial contact; smaller knee and ankle flexion (p < 0.001) at midstance; and greater hip extension at toe-off (p < 0.001). Conclusion: HIIT sessions including runs for 15-90 s and performed at intensity above the velocity associated with maximal oxygen uptake did not consistently perturb the running kinematics of trained endurance runners. Keywords: Biomechanics, Fatigue-induced, Runners, Running, Training, Two-dimensional